2016
DOI: 10.1080/17441692.2016.1202298
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Zambian prison health system: An analysis of key structural determinants

Abstract: Health and health service access in Zambian prisons are in a state of 'chronic emergency'. This study aimed to identify major structural barriers to strengthening the prison health systems. A case-based analysis drew on key informant interviews (n = 7), memos generated during workshops (n = 4) document review and investigator experience. Structural determinants were defined as national or macro-level contextual and material factors directly or indirectly influencing prison health services. The analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 10 publications
2
38
0
3
Order By: Relevance
“…through brief in-service training to improve knowledge of TB diagnosis and treatment among health workers), these components are all equally important elements of a health system capable of providing routine and sustained access to high-quality health services [15,16]. Such a 'systems' perspective is supported by the combined experience of the authors and suggests that NGOs, while important partners to the prison service and capable of providing catalytic support, are ill-positioned to take the place of government in providing routine ongoing prison health care, as (unlike in the general community) access is only possible with government permission [11].…”
Section: Discussionmentioning
confidence: 99%
“…through brief in-service training to improve knowledge of TB diagnosis and treatment among health workers), these components are all equally important elements of a health system capable of providing routine and sustained access to high-quality health services [15,16]. Such a 'systems' perspective is supported by the combined experience of the authors and suggests that NGOs, while important partners to the prison service and capable of providing catalytic support, are ill-positioned to take the place of government in providing routine ongoing prison health care, as (unlike in the general community) access is only possible with government permission [11].…”
Section: Discussionmentioning
confidence: 99%
“…The 5.5 % death rate is comparable to the death rate observed in Uganda prison [6] but higher than the 1.4 % death rate recorded in Ethiopia [18], 1.8 % death rate recorded in South Africa [5]and 2 % death rate recorded in Brazil [4]. This high death rate could be attributed to the poor prison living conditions -overcrowding [19], poor nutrition [20] and possibly to the rate of HIV/TB co-infection without use of antiviral therapy (due to the lower coverage of antiretroviral therapy use during this time period), which has been shown to be associated with unsuccessful treatment outcome [13,21]. This study also showed that unsuccessful TB treatment outcome was associated with age greater than 35 years old.…”
Section: Discussionmentioning
confidence: 75%
“…The varied intra prison differences may be due to the high turnover of prisoners and remandees (they are not yet sentenced and can be transferred out to another facility or released into the general public where they are lost to follow up) [17]. There can be poor linkage within prison facilities and the communities as once prisoners are released into the community, they are not adequately actively followed up for continuity of treatment [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The varied intra prison differences are because of the high turnover of prisoners, remandees as these prisoners are not yet sentenced and can be transferred out to another facility or released into the general public [15]. There is also poor linkage within prison facilities and with the communities as once prisoners are released into the community they are not adequately actively followed up for continuity of treatment [18,19]. This study showed an overall 2.6 % loss to follow-up which was lower than in other studies reported in similar limited resource setting in prisons in Uganda (43.0%) [16], and Brazil (13.0%) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a retrospective study from 2007 -2011 showed that prisoners accounted for 5.7% (24,585) of the national TB registered cases with a 50% cure rate, 8% default rate, 1% death rate , 8% transfer out rate and in 30% the 'treatment outcome' field was not completed [17]. In South Africa, a retrospective study of 202 prisoners diagnosed with TB from 2007 -2009 showed a 45 % cure rate, 1% relapse rate, 0.5 % treatment failure rate, 1.8 death rate and 51% transfer out rate [18], while in Nigeria, a retrospective study of 48 prisoners diagnosed with TB from 2004 to 2008 showed a 67% treatment completion rate, 29 % transfer out rate and 4.2 % death rate [19]. In Uganda, a retrospective study of 469 prisoners diagnosed with TB from 2011 to 2012 showed a 48% treatment completion rate, 43% defaulter rate, 5% death rate and 4% still on treatment.…”
Section: Introductionmentioning
confidence: 99%